2019
DOI: 10.1007/s00540-019-02627-3
|View full text |Cite
|
Sign up to set email alerts
|

Handover of anesthesia care is associated with an increased risk of delirium in elderly after major noncardiac surgery: results of a secondary analysis

Abstract: In patients undergoing major surgery, complete handover of intraoperative anesthesia care is associated with adverse postoperative outcomes including high mortality and more major complications. The purpose of this study was to explore the association between the intraoperative complete handover between anesthesiologists and the occurrence of postoperative delirium. This was a secondary analysis of the database of a previously published clinical trial. Seven hundred patients aged 65 years or older, who were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…A 2020 systematic review 1 identified 6 quantitative studies on the potential impact of anesthesiology handover on more than 600 000 patients who underwent mostly noncardiac surgery. Of these studies, 5 demonstrated adverse outcomes associated with handover 2,3,[33][34][35] and 1 demonstrated a lack of association. 34,36 In their exploratory meta-analysis of 3 noncardiac studies 3,33 and 1 cardiac study, 2 the authors reported a pooled relative risk of 1.40 (95% CI, 1.19-1.65; I 2 = 98%) for mortality in patients who were exposed as compared to those not exposed to handover.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 systematic review 1 identified 6 quantitative studies on the potential impact of anesthesiology handover on more than 600 000 patients who underwent mostly noncardiac surgery. Of these studies, 5 demonstrated adverse outcomes associated with handover 2,3,[33][34][35] and 1 demonstrated a lack of association. 34,36 In their exploratory meta-analysis of 3 noncardiac studies 3,33 and 1 cardiac study, 2 the authors reported a pooled relative risk of 1.40 (95% CI, 1.19-1.65; I 2 = 98%) for mortality in patients who were exposed as compared to those not exposed to handover.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were evaluated using the NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. 4e6,9,15e17 The overall quality rating was 'good' for four of the studies 3,5,16,17 and 'fair' for the other four studies. 4,6,9,15 Ratings are included in Table 1.…”
Section: Risk Of Biasmentioning
confidence: 95%
“…Specifically, handover was associated with greater risk of in-hospital mortality, 4,5 major morbidity, 4,5 postoperative complications, 3,6,16 all-cause mortality at 30 days, 3 admission to ICU, 3 length of stay, 3 extended postoperative ventilation, 3 wound dehiscence, 3 bleeding, 3 pneumonia, 3 unplanned return to OR, 3 new onset haemodialysis, 3 and postoperative delirium. 17 A list of confounders accounted for by each of these studies is provided in Supplementary Appendix 2.…”
Section: Association Of Anaesthesia Handovers With Patient Outcomementioning
confidence: 99%
“…PubMed search shows that more than 140 articles on postoperative delirium (POD) have been published (28 articles in anesthesia journals) between January 1 and April 30, 2019. Two such articles regarding POD were published in the February issue of this journal [1,2]. These articles raised two perioperative risk factors for POD, handover of anesthesia care [1] and postoperative hypotonic fluid administration [2].…”
Section: Introductionmentioning
confidence: 99%
“…Two such articles regarding POD were published in the February issue of this journal [1,2]. These articles raised two perioperative risk factors for POD, handover of anesthesia care [1] and postoperative hypotonic fluid administration [2]. As handover of anesthesia care for long-duration surgery is inevitable, this facet of POD may be difficult to reduce.…”
Section: Introductionmentioning
confidence: 99%